2018
DOI: 10.1002/ana.25151
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of transcranial direct current stimulation for poststroke dysphagia

Abstract: Application of tDCS over the contralesional swallowing motor cortex supports swallowing network reorganization, thereby leading to faster rehabilitation of acute poststroke dysphagia. Early treatment initiation seems beneficial. tDCS may be less effective in right-hemispheric insulo-opercular stroke. Ann Neurol 2018;83:328-340.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
100
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 50 publications
2
100
0
1
Order By: Relevance
“…on PS-OD. [9][10][11]32 In general terms, pharyngeal M1-rTMS, mainly in the contralesional hemisphere, is the most effective neurostimulation strategy to promote clinical recovery, with positive results pointing tentatively toward to "excitation" rather than "inhibition" for a better outcome, although this last issue is still under discussion. 9,10,[34][35][36][37][38] However there are no studies assessing the effect of rTMS on the sensory cortex (S1) for the treatment of OD as we have evaluated in this paper.…”
Section: Central Neurostimulation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…on PS-OD. [9][10][11]32 In general terms, pharyngeal M1-rTMS, mainly in the contralesional hemisphere, is the most effective neurostimulation strategy to promote clinical recovery, with positive results pointing tentatively toward to "excitation" rather than "inhibition" for a better outcome, although this last issue is still under discussion. 9,10,[34][35][36][37][38] However there are no studies assessing the effect of rTMS on the sensory cortex (S1) for the treatment of OD as we have evaluated in this paper.…”
Section: Central Neurostimulation Strategiesmentioning
confidence: 99%
“…9,10 One recent randomized controlled trial (RCT) using contralesional tDCS in acute PS-OD showed that functional recovery of swallowing was accompanied by increased activation of the swallowing network in the stimulated hemisphere supporting neuronal reorganization as the leading mechanism to achieve faster rehabilitation. 11 Approaches to improve swallow function currently under research have shown promising results in older and PS patients with OD and include the activation of the sensory pathway through peripheral transcutaneous or intra-pharyngeal electrical stimulation (IPES) or chemically with transient receptor potential (TRP) oral agents. [12][13][14] IPES has been found specifically valuable to treat severely affected tracheostomized PS-OD patients by increasing the proportion of patients who were ready for decannulation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these hurdles, the current study by Suntrup‐Krueger and colleagues offers hope to stroke survivors with dysphagia that swallowing functions can be improved beyond the natural recovery effects in the early poststroke phase. Enhancing and facilitating swallowing functions in the acute stroke phase might have long‐term care and economic effects, particularly because length of stay is frequently determined by a stroke patient's swallow status and the need of a direct enteral feeding tube.…”
mentioning
confidence: 99%
“…In the February issue of the Annals of Neurology , Suntrup‐Krueger and colleagues presented the results of a double‐blind, randomized study of 60 acute dysphagic stroke patients receiving either contralesional anodal (1mA, 20 minutes) or sham transcranial direct current stimulation (tDCS) on 4 consecutive days, both combined with simultaneous swallowing exercises.…”
mentioning
confidence: 99%
See 1 more Smart Citation